If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-9+3x=1/2(18+6x)
We move all terms to the left:
-9+3x-(1/2(18+6x))=0
Domain of the equation: 2(18+6x))!=0We add all the numbers together, and all the variables
x∈R
3x-(1/2(6x+18))-9=0
We multiply all the terms by the denominator
3x*2(6x+18))-(1-9*2(6x+18))=0
Wy multiply elements
6x^2(6-18x(6=0
| 2(b-1)+3b=3 | | 35+14x=28 | | k/4+5=19 | | 0.4w(6w-10)+1.5w=24.08 | | -32x-20=9x-26 | | 29/18+1/2=-5/3(x+1/3) | | X+27+97+x=180 | | a+1=a+4-83 | | -4(2+7n)+2n=148 | | -16g=272 | | Tn=8-4 | | 7x=4.20 | | 12x+4x=18 | | 2{3y-6}=42 | | a+1=a+4 | | 2x+4/x=6/5 | | 24=4+f | | 4(2x-6)=80 | | -5x+6=-18 | | -9n=3n-10 | | 6x+5=8(x+4) | | 4m-14=10 | | 3÷5x+8=29 | | 6r+3=r+12 | | 3÷5x=8=29 | | 6x+14=90° | | 2x+5+3x-1+8=10 | | 20x+4=x | | x=240/125 | | (4-3x)(10-9x)=0 | | 2y-4(3y+5)=-50 | | 4x+3(2x-8)=26 |